Investigation of the effect of pH environment on the properties of magnetite nanoparticles used in nano drug delivery production prepared by co-precipitation method - Ebadi, Mona; Saifullah, Bullo; Hussein, Mohd Zobir (2018)
In the present work, magnetic nanoparticles coated with polyethylene glycol and anticancer liver drug in different pH 4 and 8 were synthesized by co-precipitation method. In order to synthesize magnetic nanoparticles, from polyethylene glycol as a stabilizing agent and 5-fluorouracil for anticancer liver agent were used. We have tried to investigate the effect of PH in two acidic and alkaline environments (PH 4 and PH 8) on the properties of coated nanoparticles in drug delivery. Magnetite nanoparticles were first synthesized. In the following, magnetite nanoparticles have been synthesized in anti-cancer drug was intercalated into the interlayer of the layered double hydroxide (LDH). Eventually, changed PH in two acidic and alkaline environments. Structural and magnetic properties of magnetic nanoparticles were investigated by XRD and VSM. The X-ray diffraction results showed that, the sample is composed of iron oxides which construct the core. VSM analysis of synthesized samples in pH 4 and pH 8 showed superparamagnetic property with magnetic saturation values of 27 and 40 emu/g, respectively.